“Hold on, do I really need this?”: Countering impulse clothing purchases through short reflections - Maja Grünzner; Isabell Richter; Mathew P. White; Sabine Pahl (Cleaner and Responsible Consumption)
Fast fashion deliberately targets young consumers' purchase impulse tendencies. It is based on a poor-quality production, high turnover model and has quickly become a major contributor to clothing-related pollution worldwide. This study examines whether reflection tasks can reduce young consumers' (aged 18–34) purchase impulses and if environmental considerations influence their decisions. Using a pre-registered online experimental vignette study with a between-participant design, 1123 UK-based young consumers were randomly allocated to one of three reflection tasks or a control group. The tasks involved (1) thinking of general reasons not to buy (Reflection Neutral), (2) thinking of reasons not to buy including environmental considerations (Reflection Environment) or (3) recalling a happy memory with a favourite clothing item (Reflection Desire). Findings revealed that participants in Reflection Neutral and Reflection Environment conditions reported significantly lower purchase desire and purchase likelihood compared to the control group, with no significant difference between these two conditions. Reflection Desire did not reduce purchase desire or likelihood compared to the control. These results suggest that targeted reflection tasks, particularly those involving reasons not to buy a clothing piece, have the potential to promote more sustainable consumption behaviours. Real-world validation of these findings could contribute to efforts to reduce fast fashion's environmental impact.